Chemistry : a modern course - Smoot, Robert C.; Price, Jack S.; Smith, Richard G. (Columbus : Charles E. Merrill Publishing Company, 1983)
The text takes into consideration a realistic appraisal of the capabilities and maturities of typical students. We wish to express our sincere thanks to the many chemistry students, teachers, and science educators who have made suggestions for changes based on their use of Chemistry: A modern Course.
Chapter 1. Nature, chemistry and you -- 2. Measuring and calculating -- 3. Matter -- 4. Chemical formulas -- 5. The mole -- 6. Chemical equations -- 7. Quantitative relationships -- 8. Atomic structure -- 9. Electron clouds and probability -- 10. Periodic table.
Includes bibliographical references and index.
Keywords: CHEMISTRY